Culture of excellence for better internal service quality in high education / Nasriman Abdul Rahman, Boo Ho Voon and Firdaus Abdullah - Abdul Rahman, Nasriman; Voon, Boo Ho; Abdullah, Firdaus (Universiti Teknologi MARA, 2021)
The institutions of higher learning are required to provide excellent service to both their internal and external customers. This is a challenge to most of the public universities. In order to achieve this, they need to know and understand the elements that contribute to this excellence. The employees play an important role in providing the best quality of work and serve their customers (e.g., students). The consistently outstanding work performance coupled with the right attitudes among employees help to transform the norm into a culture of excellence (CoE). Good co-ordination and relationship among the management teams and employees will help to serve the employees better. This research aims to help the management teams of the public universities to cultivate and hopefully sustain the CoE for institutional excellence. The dimensions and items of the variables were derived from the related literature and focus group interviews. The structured questionnaire was then designed. The CoE consisted of eight (8) dimensions and 71 items, relevant for the public universities. A measurement model using Smart PLS was developed and the relationship between CoE and internal service quality was investigated. Several implications and recommendations were discussed and proposed for the public universities.